Manfaat Media Sosial Facebook dalam Meningkatkan Volume Penjualan pada Usaha Online Shop Preloved Merry Shop: Studi Kasus Merry Shop di Desa Buyumpondoli Kecamatan Pamona Puselemba Kabupaten Poso - Ruth Dora Yunia Kopi; Marthen Sangkide; Yulian Rinawaty Taaha; Sanny Feria Juliana; Feliks Arfid Guampe (AKUNTANSI 45, 2024)
This study aims to assess the effectiveness of using social media, particularly Facebook, in increasing sales volumes at the Merry Shop online preloved store. The research object is the marketing and sales activities at Merry Shop, which uses Facebook as the main platform for interacting with consumers. The methodology employed is a qualitative approach, with a case study as the research design. Data were collected through interviews, observations, and documentation from September to November 2023 in Buyunpondoli Village, Pamona Puselemba District, Poso Regency. Data analysis was conducted using qualitative descriptive methods, focusing on the use of social media, identifying supporting and inhibiting factors, and evaluating sales improvements. The findings indicate that the use of Facebook has significantly expanded Merry Shop’s market reach and enhanced interactions with customers, which has contributed to an increase in sales volumes. This platform allows the business to offer products effectively at a lower cost compared to traditional promotional methods. However, challenges such as product mismatches and consumer trust issues remain obstacles that need to be addressed to maximize sales potential. The study concludes that effective marketing strategies and accurate market targeting through social media can improve the sales performance of online businesses, especially in the preloved or second-hand goods sector.